precal
posted by Anonymous .
secx/sinxsinx/cosx=cotx

precal 
Steve
sec/sin = 1/sin*cos
1/sin*cos  sin^2/sin*cos
= (1sin^2)/sin*cos
= cos^2/sin*cos
= cos/sin
= cot
Respond to this Question
Similar Questions

Math
Verify the identity . (cscXcotX)^2=1cosX/1+cosX _______ sorry i cant help you (cscXcotX)=1/sinX  cosX/sinX = (1cosX)/sinX If you square this you have (1cosX)^2/(sinX)^2 Now use (sinX)^2 = 1  (cosX)^2 to get (1cosX)^2 / 1  … 
PreCalc
Trigonometric Identities Prove: (tanx + secx 1)/(tanx  secx + 1)= tanx + secx My work so far: (sinx/cosx + 1/cosx + cosx/cosx)/(sinx/cos x  1/cosx + cosx/cosx)= tanx + cosx (just working on the left side) ((sinx + 1  cosx)/cosx)/((sinx … 
trig
express this in sinx (1/ cscx + cotx )+ (1/cscx cotx) i got 2sinx is that right? 
Trigonometry.
( tanx/1cotx )+ (cotx/1tanx)= (1+secxcscx) Good one! Generally these are done by changing everything to sines and cosines, unless you see some obvious identities. Also generally, it is best to start with the more complicated side … 
drwls
My previous question: Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity. (secx/sinx)*(cotx/cscx) = (secx/cscx)(cotx/sinx) = (sinx/cosx)*cotx*(1/sinx) "The last steps should be obvious" Not to me. I can convert (sinx/cosx) to … 
precal
1/tanxsecx+ 1/tanx+secx=2tanx so this is what I did: =tanx+secx+tanxsecx =(sinx/cosx)+ (1/cosx)+(sinx/cosx)(1/cosx) =sinx/cosx+ sinx /cosx= 2tanxI but I know this can't be correct because what I did doesn't end as a negatvie:( … 
Math
Im really struggling with these proving identities problems can somebody please show me how to do these? 
Math
I'm only aloud to manipulate one side of the problem and the end result has to match the other side of the equation Problem 1. sinx + cosx + sinx + tanx + cosxcotx = secx + cscx Problem 2. ((sinx + cosx)/(1 + tanx))^2 + ((sinx  cos^2x)/(1 … 
trigonometry
can i use factoring to simplify this trig identity? 
Precalculus/Trig
I can't seem to prove these trig identities and would really appreciate help: 1. cosx + 1/sin^3x = cscx/1  cosx I changed the 1: cosx/sin^3x + sin^3x/sin^3x = cscx/1cosx Simplified: cosx + sin^3x/sin^3x = cscx/1cosx I don't know …